2011
DOI: 10.1177/1947601911416357
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of c-Myc in Acute Myeloid Leukemia Involving Direct Regulation of miR-26a and Histone Methyltransferase EZH2

Abstract: Increased expression or aberrant activation of c-Myc plays an important role in leukemogenesis. Here, we show that in acute myeloid leukemia (AML), c-Myc directly controls the expression of EZH2, a component of the Polycomb repressive complex 2, and miR-26a. miR-26a is downregulated in primary blasts from AML patients and, during myeloid differentiation of AML cells, is induced together with a decrease in c-Myc and Ezh2 levels. Previously, EZH2 was shown to be regulated by miR-26a at the translational levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 31 publications
3
93
0
Order By: Relevance
“…50 Interestingly EZH2, a component of Polycomb repressive complex, found to be mutated in 1 patient in this study, is known to be directly controlled by MYC in AMLs. 51 Our study cannot of course rule out other driver hits conferred by epigenetic events. A previous transcriptome comparison found the expression of testis-cancer antigen PRAME as the discriminative marker of DS AMKL compared with DS TMD, 44 and the overexpression of this gene is known to be due to demethylation of the regulatory regions and is established as a potential driver event in tumorigenesis 52 and inhibitor of differentiation in myeloid leukemic precursor cells.…”
Section: Discussionmentioning
confidence: 97%
“…50 Interestingly EZH2, a component of Polycomb repressive complex, found to be mutated in 1 patient in this study, is known to be directly controlled by MYC in AMLs. 51 Our study cannot of course rule out other driver hits conferred by epigenetic events. A previous transcriptome comparison found the expression of testis-cancer antigen PRAME as the discriminative marker of DS AMKL compared with DS TMD, 44 and the overexpression of this gene is known to be due to demethylation of the regulatory regions and is established as a potential driver event in tumorigenesis 52 and inhibitor of differentiation in myeloid leukemic precursor cells.…”
Section: Discussionmentioning
confidence: 97%
“…Host HSCs can be distinguished from transplanted cells on the basis of CD45 isoforms, as shown in Figure 6A inhibitory effect on MYC. Concurring with the emerging role of MYC in AML (59,60), perphenazine, the only phenothiazine hit in AML in the present study, was revealed as a top hit in a chemical screen for suppressors of MYC-induced T-ALL in zebrafish (35). Finally, the multiparametric screening assay described here could potentially allow for the identification of compounds that restore cell differentiation in T-ALL, as exemplified by the differentiation therapy achieved in acute promyelocytic leukemia (61).…”
Section: -Me2 Kills Leukemic Blasts Without Affecting Viability Of Nmentioning
confidence: 91%
“…However, differently from BE(2)-C cells, the D283 Med cell line originates from human Medulloblastoma, a tumor of the CNS. Moreover, we used two human Acute Promyelocytic Leukemia (APL) cell lines, the NB4 and HL-60 cells, induced to granulocytic differentiation by RA-treatment 32 . Further, we tested linc-NeD125 expression in human primary myoblasts differentiated to myotubes.…”
Section: Resultsmentioning
confidence: 99%
“…HL-60 (ATCC Ò CCL ¡ 240 TM ) and NB4 cell lines were cultured and differentiated with RA as described in Salvatori et al, 2011. 32 Myoblasts were treated as indicated in Ballarino et al, 2015. 33 Plasmids were transiently transfected into untreated or RAtreated BE(2)-C cells by Lipofectamine and Plus Reagent (Invitrogen) in OPTI-MEM I medium (Gibco), according to manufacturer's directions.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%